Hubungan antara Kepemilikan Keluarga dengan Kesuksesan Bisnis pada Usaha Kecil & Menengah (UKM) - Arista Natia Afriany; Adelia Nurliani Afiani Putri; Dekeng Setyo Budiarto (Universitas Sarjanawiyata Tamansiswa, 2019)
The relationship between small firm ownership and performance is an interesting issue, especially in accounting literature. The purpose of this study is to examine whether there are business success differences in SMEs based on ownership. The respondents of this study were 120 SMEs owners in Yogyakarta. The sampling technique uses purposive sampling with criteria based on the act No. 20/ 2008 concerning SMEs. The research hypothesis was tested with One Way ANOVA to prove the relationship between ownership and business success in SMEs. The results showed that there were significant differences between family ownership and non-family ownership in business success. The results of this study have implications for non-family SME owners in order to improve performance so they can compete with other SMEs.